2009
DOI: 10.1039/b904403e
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights into a copper–disulfide interaction in oxidation of imines by disulfides

Abstract: The concept of using disulfides as an oxidant for Cu(i) is introduced as part of a Cu-catalyzed process leading to the formation of benzothiazole from an iminodisulfide under an inert atmosphere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…The centerpiece of the method is the interaction between a disulfide moiety and a thiophilic metal – an interaction that enjoys growing attention in synthetic organic chemistry and biological chemistry alike 7. In our previous work, we examined the origin of the above chemistry in the Cu‐catalyzed intramolecular oxidation of imines by disulfides under anaerobic conditions 8. It was found that the substrate 1 smoothly transformed, under the above conditions, into the products 2 and 3 in 1:1 ratio, and, based on our experiments, corroborated by the gas‐phase data, a concise mechanism of the transformation was suggested, invloving the C–H bond activation as the rate‐limiting step (see Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…The centerpiece of the method is the interaction between a disulfide moiety and a thiophilic metal – an interaction that enjoys growing attention in synthetic organic chemistry and biological chemistry alike 7. In our previous work, we examined the origin of the above chemistry in the Cu‐catalyzed intramolecular oxidation of imines by disulfides under anaerobic conditions 8. It was found that the substrate 1 smoothly transformed, under the above conditions, into the products 2 and 3 in 1:1 ratio, and, based on our experiments, corroborated by the gas‐phase data, a concise mechanism of the transformation was suggested, invloving the C–H bond activation as the rate‐limiting step (see Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…This is often a problem in searching for copper (III) intermediates and more studies are necessary in this direction. Srogl et al have investigated copper catalyzed disproportionation of iminedisulfides (Scheme 17) from both synthetic and gas-phase perspectives (Srogl et al, 2009). For the ESI-MS studies the reactant 1 was mixed with a copper(I) catalyst and sprayed into the a mass spectrometer.…”
Section: Copper Catalyzed Coupling Of Thiols With Aryl Halidesmentioning
confidence: 99%
“…the ionization process is believed to impose only a small energy to the species transferred to the gas phase, and therefore the gaseous ions often reflect the species contained in the sprayed solution). Moreover, ESI‐MS appears to be the most convenient method for a successful investigation of organometallic compounds in the gas phase and, in numerous cases, was successfully applied for studying organometallic reaction mechanisms …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ESI-MS appears to be the most convenient method for a successful investigation of organometallic compounds in the gas phase and, in numerous cases, was successfully applied for studying organometallic reaction mechanisms. [31][32][33][34][35][36][37][38][39][40][41][42] Reactions involving boronic acids play an important role as these acids are stable, commercially available reagents with relatively low toxicity. [43,44] Their application is most popular in Suzuki couplings, where palladium complexes are applied as catalysts.…”
Section: Introductionmentioning
confidence: 99%